Pelatihan Aplikasi Olah Data SmartPLS untuk Meningkatkan Skill Penelitian bagi Dosen Sekolah Tinggi Theologia Batam - Tambun, Sihar; Heryanto, Heryanto; Mulyadi, Mulyadi; Sitorus, Riris Rotua; Putra, Robiur Rahmat (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to improve the research skills of lecturers in research data processing through Smart PLS training. The output target of the activity is that the participants can independently process research data and understand how to read the results and their interpretation. The training used the lecture and the practical method. The number of training participants was 20 lecturers from five STTs in Batam. The activity evaluation instruments were questions made on the Google Form that the participants must answer. The data analysis compared the participants’ abilities before and after this training. The training evaluation results proved an increase in the ability of the participants to use the Smart PLS software. First, the participants already understand how to process data to test the data’s validity and reliability. Second, the participants already understood how to test the intervening model hypothesis. Then, the participants understood how to test the moderating model’s hypothesis. Thus, participants’ research skills have improved significantly after attending this training. This type of training, particularly practice-based training, should be held on an ongoing basis.